Preparation method of bimetallic nano-microsphere self-supporting oxygen production catalyst

The preparation of bimetallic nanometer microspheres self-supported oxygen production catalysts through a simple one-step electrodeposition method, solving the problems of high overpotential of the oxygen evolution reaction and high cost of noble metal catalysts, achieving high activity, low cost and high efficiency catalytic effects, and having good commercial prospects.

CN119571378APending Publication Date: 2025-03-07LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411765705.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, the overpotential of the oxygen evolution reaction (OER) during the electrolytic oxidation process of water hinders the development of the electrolytic hydrogen production process, and the scarcity and high cost of precious metal-based catalysts limit large-scale commercial applications.

Method used

A one-step simple electrodeposition method was used to prepare a self-supported oxygen production catalyst for bimetallic nanometer microspheres. The catalyst was prepared by dissolving pure Fe and pure Co in an ammonia sodium citrate environment and combining nickel foam as a substrate.

Benefits of technology

It has achieved low-cost, non-toxic, high-activity and high chemical stability catalysts, significantly reducing the overpotential of the oxygen evolution reaction, improving catalytic activity and conversion efficiency, and having good commercialization prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571378A_ABST
    Figure CN119571378A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical oxygen-producing catalyst materials, and particularly relates to a preparation method of a bimetallic nano-microsphere self-supporting oxygen-producing catalyst, which comprises the following steps: dissolving pure Fe and pure Co according to a certain mass ratio and sodium chloride in water in an ammoniacal sodium citrate environment, heating at constant temperature, magnetically stirring to obtain transparent liquid, taking foamed nickel as a working electrode, and preparing the bimetallic nano-microsphere self-supporting oxygen-producing catalyst. The preparation method comprises the following steps: taking nickel foam as a substrate, taking a platinum sheet and a saturated calomel electrode as a counter electrode and a reference electrode, depositing for 100-150 minutes at 20-50 DEG C under the current density of-200 to-150 mA cm <-2 >, washing the surface of the nickel foam with deionized water after electro-deposition is completed, and carrying out vacuum drying to obtain the black nano-microporous microsphere Fe-Co material loaded on the nickel foam. According to the present invention, the microporous structure enables the catalyst to have more catalytic activity sites and more specific surface area, and the compact coating with the crystal structure perfectly matches the foamed nickel matrix and does not easily fall off, such that the catalyst has characteristics of rapid reaction kinetics and excellent durability, and the valuable guidance is provided for the reasonable development of the high-performance oxygen production catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical oxygen production catalyst materials, and in particular relates to a method for preparing a bimetallic nano-microsphere self-supporting oxygen production catalyst. Background Art

[0002] With the increasing application of hydrogen energy in various fields, and its high energy density, zero pollution, zero emission, and good regeneration, the electrolysis of water to produce hydrogen has become urgent. The oxygen evolution reaction (OER) in the water electrolysis oxidation process involves slow four-proton coupled electron transfer, which greatly hinders the development of the electrolysis of water to produce hydrogen. Therefore, how to reduce the overpotential of OER is an urgent problem to be solved.

[0003] So far, precious metal-based catalysts such as platinum, iridium, and ruthenium have shown excellent catalytic activity, but their scarcity and high cost have seriously hindered large-scale commercial applications. In recent years, researchers have developed a large number of non-precious metal-based OER catalysts, such as transition metal nitrides, phosphides, chalcogenides, and carbides, due to their good catalytic activity and high abundance in order to reduce the investment cost and scale limitations of hydrogen production and enrich the types of catalysts.

[0004] Among the three-dimensional transition metal catalysts used for oxygen evolution reaction (OER), cobalt-based materials have attracted great interest due to their good catalytic activity in alkaline environments, low cost, structural versatility, and good absorption capacity for reaction intermediates. By adding nickel, iron, copper, nitrogen, boron, and phosphorus, structures such as CoOOH, CoOOH, and CoO2 can be formed, or binary and ternary metal compounds can be formed to further improve the catalytic activity. Among them, since Fe can better regulate the electronic structure of Co, thereby improving the oxygen evolution activity of Co-based catalysts, it is expected to develop more potential oxygen evolution catalysts together with Co. Therefore, choosing the right method and the right material can maximize the catalytic activity of Co-based catalysts. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a nano-microsphere self-supporting oxygen-generating catalyst material and a preparation method thereof by a simple one-step electrodeposition method. The catalyst prepared by the present invention has the characteristics of low cost, non-toxicity, high activity and high chemical stability.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a bimetallic nanosphere self-supporting oxygen-generating catalyst comprises the following steps:

[0008] 1) Pretreatment of nickel foam: cutting the nickel foam into small pieces, ultrasonically cleaning in acetone, anhydrous ethanol and deionized water respectively to remove grease, impurities and oxide layer on the surface of the nickel foam sample, and vacuum drying the cleaned nickel foam sample;

[0009] 2) Preparation of electrodeposition solution: dissolve pure Fe, pure Co and sodium chloride (sodium chloride is added to enhance the conductivity of the solution) in 80-120 mL of deionized water in an ammoniacal sodium citrate environment, add all chemicals into the electrolytic cell, heat at a constant temperature and stir with magnetic force until a transparent solution is obtained, which is the electrodeposition solution;

[0010] 3) Cleaning the nickel foam substrate: ultrasonically clean the nickel foam treated in step 1) with a hydrochloric acid solution, and then wash the nickel foam sample with a large amount of distilled water for multiple times to remove the hydrochloric acid remaining on the surface thereof, and quickly air-dry the cleaned nickel foam with a hair dryer, and then immediately immerse it in the electrodeposition solution of the electrolytic cell;

[0011] 4) Preparation of Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst by electrodeposition in a three-electrode system: nickel foam was used as the working electrode, platinum sheet and saturated calomel electrode were used as the counter electrode and reference electrode, and the current density was set to -200~-150mAcm -2 , deposited at 20-50°C for 100-150 minutes; after the electrodeposition is completed, the surface of the nickel foam sample is rinsed with deionized water and vacuum dried to obtain a Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst.

[0012] Furthermore, in the above preparation method, in step 1), the nickel foam with a thickness of 1 mm is cut into small pieces of 1 cm×1.5 cm.

[0013] Furthermore, in the above preparation method, in step 1) and step 3), the ultrasonic cleaning is performed at 20-40° C. for 10-20 minutes, and the cleaning power is 800-1000W.

[0014] Furthermore, in the above preparation method, in step 1), the vacuum drying is carried out at 30-60° C. for 10-15 hours.

[0015] Furthermore, in the above preparation method, in step 2), the mass of pure Fe accounts for 12%-20% of the total mass of pure Fe and pure Co.

[0016] Preferably, in step 2), the mass of pure Fe accounts for 80%-88% of the total mass of pure Fe and pure Co (ie, the atomic ratio of Fe to Co is 1:5 after a simple electrodeposition step).

[0017] Furthermore, in the above-mentioned preparation method, in step 2), the conditions of the constant temperature heating magnetic stirring are: temperature of 20-50° C., and rotation speed of 10-30 rpm.

[0018] Furthermore, in the above preparation method, in step 3), the concentration of the hydrochloric acid solution is 5-8 mol L -1 .

[0019] Furthermore, in the above preparation method, in step 4), the vacuum drying is carried out at 30-50° C. for 30-120 minutes.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention uses a one-step simple electrodeposition method to controllably prepare a nano-microsphere self-supporting Fe-Co catalyst, which can save the tedious steps of coating the catalyst suspension on a glassy carbon electrode or a carbon cloth, significantly improve its conductivity, and can directly test its performance, which is simple and convenient.

[0022] 2. The present invention can control microporous structures of different morphologies by changing different electrodeposition currents, electrolyte ratios, electrodeposition time, etc., and prepare nanoscale microsphere materials through a one-step simple electrodeposition method. The catalyst coating formed is relatively flat as a whole, and the catalyst is in the shape of a relatively uniform microsphere with a small number of small holes on it. The presence of the small holes is considered to be a continuous channel from the substrate to the interface composed of bubbling hydrogen generated by the cathode reaction on the nickel electrode. The presence of small holes is conducive to better storage of hydrogen energy, providing more active sites, providing a larger catalytic specific surface area, giving the catalyst superior super-oxygen-repellent properties, effectively alleviating the problem of bubble adhesion, and generally promoting long-term continuous and effective hydrogen and oxygen evolution reactions, which is conducive to improving catalytic activity.

[0023] 3. The Fe-Co catalyst prepared by the present invention through a one-step simple electrodeposition method has a simple process flow and is easy to operate compared with other chemical synthesis methods. It can reduce waste liquid pollution to a certain extent and is economical and environmentally friendly. Electrodeposition is assisted in an ammoniacal sodium citrate system to obtain a catalyst with high catalytic activity. The raw materials for preparation are cheap and easy to obtain, which is more conducive to expanded commercial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the Fe-Co bimetallic nanosphere self-supporting oxygen-producing catalyst prepared in Example 1 of the present invention.

[0025] Figure 2 This is a schematic diagram of a one-step simple electrodeposition electrolytic cell according to Example 1 of the present invention.

[0026] Figure 3 This is the XRD diagram of the Fe-Co bimetallic nanosphere self-supporting oxygen-producing catalyst prepared in Example 1 of the present invention.

[0027] Figure 4This is a TEM image of the Fe-Co bimetallic nanosphere self-supporting oxygen-producing catalyst prepared in Example 1 of the present invention.

[0028] Figure 5 The current density of Example 1 of the present invention is 300 mA cm -2 A graph showing the amount of oxygen collected over time.

[0029] Figure 6 It is the LSV curve diagram of the Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] Example 1

[0031] (I) Preparation method

[0032] 1) Pretreatment of nickel foam: nickel foam (NF) with a thickness of 1 mm was cut into small pieces of 1 cm × 1.5 cm, and ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 minutes at room temperature (power of 900 W) to remove grease, impurities and oxide layer on the surface of the nickel foam sample. The cleaned nickel foam sample was placed in a vacuum drying oven and dried at 50° C. for 12 h;

[0033] 2) Preparation of electrodeposition solution: weigh 0.6758 g of pure iron (Fe), 5.1892 g of pure cobalt (Co), a total of 5.865 g of pure iron and pure cobalt, and then weigh 1.7532 g of sodium chloride (NaCI) and 8.823 g of sodium citrate (C6O7H5Na3·2H2O), dissolve them in 100 mL of water, and add 25 mL of 0.3% ammonia water (NH3·H2O), add all the chemicals into the electrolytic cell, heat at a constant temperature of 30°C and 15 r / min with magnetic stirring until a transparent solution is obtained, which is the electrodeposition solution.

[0034] 3) Cleaning the nickel foam substrate: Wash the nickel foam treated in step 1) with 6 mol L -1 The hydrochloric acid solution was ultrasonically cleaned at room temperature for 15 minutes (power was 900 W), and then the foam nickel sample was cleaned several times in an ultrasonic machine with a large amount of distilled water to remove the hydrochloric acid remaining on its surface. The cleaned foam nickel was quickly air-dried with a hair dryer and then immediately immersed in the electrodeposition solution of the electrolytic cell.

[0035] 4) Preparation of Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst by electrodeposition in a three-electrode system: nickel foam was used as the working electrode, platinum sheet and saturated calomel electrode were used as the counter electrode and reference electrode, and the current density was set to -180 mA cm -2 , deposited at 30 °C for 120 min.

[0036] 5) After the electrodeposition is completed, the surface of the nickel foam sample is rinsed with deionized water and dried in a vacuum drying oven at 30° C. for 120 minutes to obtain a Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst.

[0037] Figure 1 The SEM images of Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst are at magnifications of 1k, 2K, 5K and 20K. From the images, we can see that the coating is relatively flat overall, the shape of the catalyst is a relatively uniform microsphere, and the small number of small holes on it can expose more active sites.

[0038] Figure 3 The XRD pattern of Fe-Co bimetallic nanosphere self-supported oxygen production catalyst is shown in Figure 2. The XRD spectrum is consistent with CoFe (PDF#49-1568) and Co (PDF#15-0806). The sample has six obvious diffraction peaks, which are the (110), (200) and (211) crystal planes of CoFe and the (111), (200) and (220) crystal planes of Co, indicating that iron and cobalt are successfully loaded on nickel foam by electrodeposition.

[0039] Figure 4 The TEM image of the Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst. The low-magnification TEM morphology and HRTEM image of the deposited coating are shown respectively. It can be seen from the figure that the deposited layer is distributed relatively evenly. The HRTEM image shows clear lattice fringes, and its interplanar spacing is consistent with the crystal plane of the XRD spectrum.

[0040] Figure 5 The current density is 300 mA cm -2 The amount of oxygen collected changes with time. The Faraday efficiency is calculated to be 99.4%, which has a good conversion efficiency.

[0041] (II) Electrocatalytic performance testing

[0042] The electrocatalytic performance of the catalyst was tested at room temperature and pressure in a three-electrode system, with the electrolyte being 1M KOH aqueous solution, the Fe-Co bimetallic nanosphere self-supporting oxygen-producing catalyst as the working electrode, the Hg / HgO electrode as the reference electrode, and the carbon rod as the counter electrode.

[0043] Figure 6 This is the LSV curve of the Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst, which is used to characterize the catalytic activity of the sample. The test conditions are a three-electrode system, with Hg / HgO electrode as the reference electrode, carbon rod as the counter electrode, sample as the working electrode, and 1M KOH aqueous solution as the electrolyte. It can be seen from the image that at a current density of 10 mA cm -2Under the given conditions, the overpotential is 168mV, which is close to the overpotential of most electrode materials currently available. The lower the overpotential of water electrolysis, the higher the total voltage required for water electrolysis and the conversion efficiency of electrical energy into hydrogen energy, and the higher the oxygen production efficiency. Therefore, it has good commercial prospects.

[0044] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a bimetallic nanosphere self-supporting oxygen-generating catalyst, characterized in that: The steps include: 1) Pretreatment of nickel foam: cutting the nickel foam into small pieces, ultrasonically cleaning in acetone, anhydrous ethanol and deionized water respectively to remove grease, impurities and oxide layer on the surface of the nickel foam sample, and vacuum drying the cleaned nickel foam sample; 2) Preparation of electrodeposition solution: dissolve pure Fe, pure Co and sodium chloride in 80-120 mL of deionized water in an ammoniacal sodium citrate environment, add all chemicals into the electrolytic cell, heat at a constant temperature and stir with a magnetic force until a transparent solution is obtained, which is the electrodeposition solution; 3) Cleaning the nickel foam substrate: ultrasonically clean the nickel foam treated in step 1) with a hydrochloric acid solution, and then wash the nickel foam sample with a large amount of distilled water for multiple times to remove the hydrochloric acid remaining on the surface thereof, and quickly air-dry the cleaned nickel foam with a hair dryer, and then immediately immerse it in the electrodeposition solution of the electrolytic cell; 4) Preparation of Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst by electrodeposition in a three-electrode system: nickel foam was used as the working electrode, platinum sheet and saturated calomel electrode were used as the counter electrode and reference electrode, and the current density was set to -200~-150mAcm -2 , deposited at 20-50°C for 100-150 minutes; after the electrodeposition is completed, the surface of the nickel foam sample is rinsed with deionized water and vacuum dried to obtain a Fe-Co bimetallic nanosphere self-supporting oxygen production catalyst.

2. The preparation method according to claim 1, characterized in that: In step 1), the nickel foam with a thickness of 1 mm is cut into small pieces of 1 cm×1.5 cm.

3. The preparation method according to claim 1, characterized in that: In step 1) and step 3), the ultrasonic cleaning is carried out at 20-40°C for 10-20 minutes, and the cleaning power is 800-1000W.

4. The preparation method according to claim 1, characterized in that: In step 1), the vacuum drying is carried out at 30-60° C. for 10-15 hours.

5. The preparation method according to claim 1, characterized in that: In step 2), the mass of pure Fe accounts for 12%-20% of the total mass of pure Fe and pure Co.

6. The preparation method according to claim 5, characterized in that: In step 2), the mass of pure Fe accounts for 80%-88% of the total mass of pure Fe and pure Co.

7. The preparation method according to claim 1, characterized in that: In step 2), the conditions of the constant temperature heating magnetic stirring are: temperature of 20-50° C. and rotation speed of 10-30 rpm.

8. The preparation method according to claim 1, characterized in that: In step 3), the concentration of the hydrochloric acid solution is 5-8 mol L -1 .

9. The preparation method according to claim 1, characterized in that: In step 4), the vacuum drying is carried out at 30-50° C. for 30-120 minutes.